2014
DOI: 10.1007/978-1-4939-1538-5_27
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Bead-Based Isolation of Exosomes

Abstract: Exosomes are here defined as extracellular vesicles (EVs) in the approximate size range of 30-100 nm in diameter, and are observed in most body fluids containing typical exosomal markers such as CD9, CD63, and CD81. Potential subpopulations of exosomes can be captured by targeting these markers using magnetic beads. Magnetic beads are versatile tools for exosome isolation and downstream analysis. Here, we describe the workflow of immuno magnetic isolation and analysis of exosomes by flow cytometry, Western imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 15 publications
4
115
0
Order By: Relevance
“…To map surface epitopes, we used a previously published method (35) whereby EVs are first trapped with a large bead linked to an antibody to CD63, and then additional epitopes on the trapped EVs are assayed with standard protocols for flow cytometry. As expected, the EVs captured with the protocol were positive for CD63 (Fig.…”
Section: Selection Of Optimal Mscs and Culture Conditions For Productmentioning
confidence: 99%
“…To map surface epitopes, we used a previously published method (35) whereby EVs are first trapped with a large bead linked to an antibody to CD63, and then additional epitopes on the trapped EVs are assayed with standard protocols for flow cytometry. As expected, the EVs captured with the protocol were positive for CD63 (Fig.…”
Section: Selection Of Optimal Mscs and Culture Conditions For Productmentioning
confidence: 99%
“…Several methods of isolation have been described ranging from ultracentrifugation, density gradient centrifugation, immunoaffinity capture using magnetic beads and commercially available precipitation methods. Comparative studies using these techniques demonstrated that the purity and the quality of preparations is dependent on the source of exosomes …”
Section: Extracellular Vesicles— Isolationmentioning
confidence: 99%
“…In this regard, choosing a proper exosome membrane marker is one of the most important steps in these immunoassays. It was shown that members of the tetraspanin family, such as CD81, CD9, and CD63, that are present on the membranes of exosomes can be used for efficient immunocapture . Unlike other conventional techniques for exosome isolation, antibody‐coated magnetic beads can be used for direct exosome isolation from bodily fluids, which reduces the time‐consuming centrifugation steps.…”
Section: Isolation Of Exosomesmentioning
confidence: 99%